Role of Brassinosteroids in mango fruit ripening - Zaharah, Sakimin; Singh, Zora (International Society of Horticulture, 2012)
Brassinosteroids (BRs) are steroidal plant hormones and their implications in climacteric fruit ripening are poorly understood. An aqueous solution containing different concentrations (0, 15, 30, 45 and 60 ng g-1 FW) of epibrassinolide (Epi-BL) was applied to hard mature green ‘Kensington Pride’ mango fruit to evaluate their role in climacteric fruit ripening. Following the treatments, the fruit were allowed to ripen at ambient temperature (21±1°C). All Epi-BL treatments advanced the climacteric peak of ethylene production and respiration rate by 2 and 1 d(s) respectively and also increased climacteric ethylene production and respiration rate. In addition, Epi-BL application promoted the fruit softening and skin colour development during fruit ripening. However, at eating soft ripe stage, the fruit firmness did not differ significantly among different treatments and control. The rheological properties of pulp of ripe fruit including cohesiveness, springiness and chewiness were significantly influenced with the different concentrations of Epi-BL as compared to control. The exogenous application of BRs did not significantly affect total sugars, soluble solids concentration (SSC), titratable acidity (TA) and SSC:TA ratio of ripe fruit. In conclusion, postharvest application of Epi-BL advanced and accelerated the climacteric ethylene production and respiration rate consequently promoted fruit softening and colour development, as well as hastened fruit ripening without affecting the quality of ripe fruit.